Assessing the Influence of Flowering Plants and Landscape Composition on Host-Parasitoid Food Webs - Sataral, Mihwan; Rizali, Akhmad; Winasa, I Wayan; Triwidodo, Hermanu; Buchori, Damayanti (Bogor Agricultural University, Indonesia, 2025)
The introduction of flowering plants into agricultural landscapes can significantly impact host-parasitoid food webs, although the extent of these effects varies depending on landscape characteristics. This study examined the effects of habitat manipulation by introducing flowering plants on the complexity of herbivore-parasitoid food webs in agricultural landscapes. Using Shannon diversity, links per species, linkage density, and vulnerability, we assessed the effects of flowers planted in maize fields. Herbivore collections were conducted at 2, 4, 6, 8, and 10 weeks after planting. Bipartite network analysis identified nine host morphospecies (Lepidoptera) in maize fields, revealing eight morphospecies in fields without flowering plants and six in fields with flowering plants. Eight major parasitoids were recorded, with Paratetracnemoidea sp.1 and Telenomus remus dominating fields without flowering plants, whereas T. remus was the most prevalent in fields with flowers. Spodoptera frugiperda emerged as the dominant host in both fields, whereas Lymantriidae sp.2 was present in low numbers in both field types. These results indicate that flowering plants enhance Shannon diversity and linkage density. However, the composition of the surrounding landscape can obscure these benefits, leading to simplified food web structures as the agricultural fields expand. Our findings underscore the significance of landscape context in shaping crop-herbivore-parasitoid interactions, offering valuable insights into sustainable agricultural management practices.